Perspective: Climate Change and the Relocation of Indonesia’s Capital to Borneo - Van de Vuurst, Paige; Escobar, Luis E. (Frontiers in Earth Science, 2020)
Indonesia has recently announced the relocation of the country’s capital from the island of Java to the island of Borneo. Java’s limited sustainability is evident from extreme deforestation, biodiversity loss, intense road traffic, and high pollution. Jakarta, Indonesia’s current capital on Java, is both one of the most densely populated cities in the world, and one of the most threatened by climate change. Negative impacts upon Jakarta due to climate change could affect its economy, human health, and biodiversity. These negative factors could be transferred from Jakarta to Borneo, at least partially, during the early stages of moving the capital. Borneo currently houses one of the largest remaining forested areas in Southeast Asia and is considered to be a biodiversity hotspot. However, despite its biological importance, ~30% of Borneo has been deforested in the last 50 years. Borneo also has high rates of biological endemism, but some of its emblematic endemic species are critically endangered. We argue that Indonesia’s announcement to re-locate the capital is one of the first examples of systematic, mass migration expected to occur linked to the climate change crisis. Unless a multidisciplinary and sustainable transition is implemented, the establishment of a new capital in Borneo could be a major biodiversity catastrophe. Research is urgent in Borneo to determine the status quo of its ecosystems for a large-scale, before-after assessment of the human-footprint to better understand processes in the Anthropocene.